2016
DOI: 10.21276/sjams.2016.4.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Audiologic Evaluation in Patients with Acquired Hypothyroidism

Abstract: Hypothyroidism is a common endocrine disorder resulting from deficiency of thyroid hormone or, more rarely, from their impaired activity at tissue level. In its clinically overt form, hypothyroidism is a relatively common condition, with an approximate prevalence of 2% in adult women and 0.2% in adult men. Deficiency of the hormone has a wide range of effects, because all metabolically active cells require thyroid hormone. Aim of the study is to determine the incidence of deafness in patients suffering from go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In comparison to some other studies [6, 22, 5] we can just speculate on the divergent results. Most of the studies were done in the past, and recent studies are mostly from India and the Middle East [26, 42, 43]. This geographical variation could introduce several confounding factors, including the prevalence of occupational noise exposure, preventable infections such as chronic otitis media and meningitis, nutritional status and health-care access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to some other studies [6, 22, 5] we can just speculate on the divergent results. Most of the studies were done in the past, and recent studies are mostly from India and the Middle East [26, 42, 43]. This geographical variation could introduce several confounding factors, including the prevalence of occupational noise exposure, preventable infections such as chronic otitis media and meningitis, nutritional status and health-care access.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, we observed mostly mild and only two cases with moderate hearing impairments in both hypothyroid and control groups. In later studies, hearing examinations were usually more detailed than thyroid testing and evaluations of iodine status [6, 42, 26]. Some other nutritional factors such as single nutrients (vitamin A, B, C, D and E, and zinc, Mg, Se, iodine, and iron) are associated with hearing status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation